Coopetition within and between value networks – a typology and a modelling framework. (1st January 2014) - Golnam, Arash; Ritala, Paavo; Wegmann, Alain
This study develops a typology of coopetition in value networks, wherein a distinction is made based on two factors. Firstly, whether coopetition takes place inside a particular value network (i.e., intra-value network coopetition) or between value networks (i.e., inter-value network coopetition); and secondly, whether the nature of collaboration is focused on value leveraging or value co-creation. We present empirical examples from the global ICT sector (Amazon Services, Amazon Marketplace, AIM Alliance, and Windows Mobile Community) to illustrate the four categories identified in the typology. Each example is graphically represented using a modelling framework in order to aid the understanding of various organisational and network structures that can accommodate coopetition as a complex inter-organisational relationship. We suggest that the developed typology and modelling methodology can help researchers and practitioners to better grasp and communicate the role and benefits as well as the network and organisational structures of coopetition within and between value networks.